Kasdienio gyvenimo proza: Moišės Levino Vilnos žmonių portretai - Cammy, Justin (Colloquia, 2021)
This article introduces readers to the fiction by Moyshe Levin, a member of the Yiddish literary and artistic group Yung Vilne (Young Vilna). I argue that Levin challenged sentimental myths of Vilna as a centre of Yiddish culture by crafting naturalist fiction and reportage focused on the struggles of Vilna’s Jewish underclass and workers. In doing so, he developed a fictional universe that was directly engaged with and explored the social and political challenges of local Jewish life in the 1930s.